Improving Students' Understanding of the Essence of the Muhkamat and Mutasyabihat Verses at SD Negeri 381 Tabuyung - Supriana (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to explore effective methods for improving students' understanding of the essence of Muhkamat and Mutasyabihat verses in the Quran at SD Negeri 381 Tabuyung. Muhkamat verses, known for their clear and unambiguous meanings, and Mutasyabihat verses, which require deeper interpretation, are essential components of Islamic teachings. However, students at the elementary school level often face challenges in comprehending these verses due to their abstract nature and complex interpretations. This study investigates the use of various teaching strategies, including interactive discussions, visual aids, and contextual examples, to enhance students' ability to understand both types of verses and apply them in their daily lives. The findings of this study indicate that a student-centered learning approach, which encourages active participation and critical thinking, can significantly improve students' comprehension of these Quranic verses. By shifting from traditional teacher-led methods to more interactive, inquiry-based learning, students become more engaged and better equipped to analyze the verses. The results suggest that effective teacher-student interactions, coupled with innovative instructional strategies, can foster a deeper understanding of Islamic texts. This research contributes to the development of more effective teaching practices in Islamic education, particularly at the elementary school level, and offers insights into ways to improve religious learning outcomes.